Gender Equality in Tertiary Institutions: Importance and Barriers (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This paper discussed the concept of gender equality and the concept of tertiary education. Specifically, the paper looked at the significance of gender equality in tertiary institutions. Secondary data were used employed for the paper. The secondary data were sorted from print and online publications. This paper concluded that gender equality will lead to; the development of teaching programmes, research programmes; community services programmes, improvement in the national and international ranking of tertiary institutions, manpower development and provision of good leadership and governance in the tertiary institutions. The paper also pointed out that poor implementation of gender policy, early marriage, socio-economic status of parents, traditional beliefs, patriarchal practice and poor access to educational opportunities are barriers to gender equality in Nigerian tertiary institutions. Based on these pointed problems, the paper suggested the following; implementation of gender policies, seminars, conferences and workshops must be conducted to enlighten tertiary institutions and students about the importance of gender equality in an academic environment. Tertiary institutions Managers should ensure to maintain and implement an inclusive and diverse environment that is respectful and assign roles and responsibilities for both men and women.